WAYS TO DEVELOP INTERNATIONAL TRANSPORTATION IN THE REPUBLIC OF UZBEKISTAN - Fayzikhodjaeva, M.L. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study lies in the fact that the Republic’s foreign economic relations depend on the development of international transport corridors, increasing the efficiency of international routes, and increasing export-import operations.The purpose and objectives of the study are to identify the features of the development of multimodal routes, the identification of optimal transport corridors. The subject of the study is the study of transport corridors by expanding international freight traffic.The research methodology is based on the application of comparative sampling methods, economic-analytical and export methods.